Ultrasound guidance in regional anaesthesia principles and practical implementation - Marhofer, Peter (Oxford : Oxford University Press, 2010)
This second edition of the well-illustrated practical handbook provides a concise summary of the basics of ultrasound technology, and includes the most recent knowledge in the topic of ultrasound in regional anaesthesia.
Includes index.
Description based on print version record.
Keywords: Conduction anesthesia; Ultrasonic imaging